2017
DOI: 10.1002/ijc.31195
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study identifies the GLDC/IL33 locus associated with survival of osteosarcoma patients

Abstract: Survival rates for osteosarcoma, the most common primary bone cancer, have changed little over the past three decades and are particularly low for patients with metastatic disease. We conducted a multi-institutional genome-wide association study (GWAS) to identify germline genetic variants associated with overall survival in 632 patients with osteosarcoma, including 523 patients of European ancestry and 109 from Brazil. We conducted a time-to-event analysis and estimated hazard ratios (HR) and 95% confidence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 75 publications
4
29
0
Order By: Relevance
“…Moreover, the level of IL-33 protein has been inversely correlated with tumor grade and size in patients with pulmonary adenocarcinoma, showing an association of low IL-33 expression level with a poor prognosis ( 70 72 ). Likewise, a genome-wide association study unveiled a correlation between high IL-33 expression and a good prognosis in patients with osteosarcoma ( 73 ). However, if IL-33 can have a pro-tumor effect by directly targeting cancer cells, the tumor suppressor functions displayed by IL-33 are indirectly promulgated by immune surveillance as we will show hereafter.…”
Section: Il-33 As a Marker For Good Or Poor Prognosismentioning
confidence: 99%
“…Moreover, the level of IL-33 protein has been inversely correlated with tumor grade and size in patients with pulmonary adenocarcinoma, showing an association of low IL-33 expression level with a poor prognosis ( 70 72 ). Likewise, a genome-wide association study unveiled a correlation between high IL-33 expression and a good prognosis in patients with osteosarcoma ( 73 ). However, if IL-33 can have a pro-tumor effect by directly targeting cancer cells, the tumor suppressor functions displayed by IL-33 are indirectly promulgated by immune surveillance as we will show hereafter.…”
Section: Il-33 As a Marker For Good Or Poor Prognosismentioning
confidence: 99%
“…A recent genome-wide association study (GWAS) involving 632 OS patients, including 523 European patients and 109 from Brazilian patients, produced highly significant association of GLDC/IL33 locus at 9p24.1 with the risk of OS. Using publicly available data, Koster et al found that the OS susceptible single nucleotide polymorphism (SNP) in GLDC/IL33 locus associated with low expression of IL-33, which was also significantly correlated with poor survival in OS patients 18 . This result suggested that IL-33 might play some roles in the pathogenesis of OS.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…It turns out that low IL-33 expression is associated with poor survival in patients with osteosarcoma. 98 Interestingly, IL-33/ST2 induces osteoclast apoptosis in animal models. 99 In chronic lymphocytic leukemia and multiple myeloma, cancers that arise in bone marrow, patients have reduced IL-33 plasma expression, suggesting that loss of IL-33 may damper immune surveillance in bone marrow.…”
Section: Osteosarcoma and Bone Marrow Cancersmentioning
confidence: 99%